Reproductive output of mosses under experimental warming on Fildes Peninsula, King George Island, maritime Antarctica. Issue 1 (December 2016) - Casanova-Katny, A.; Torres-Mellado, G.; Eppley, S.
Abstract Background Mosses dominate much of the vegetation in the Antarctic, but the effect of climatic change on moss growth and sexual reproduction has scarcely been studied. In Antarctica, mosses infrequently produce sporophytes; whether this is due to physiological limitation or an adaptive response is unknown. We studied the effect of experimental warming (with Open Top Chambers, OTCs) on sporophyte production on Fildes Peninsula, King George Island for four moss species (Bartramia patens, Hennediella antarctica, Polytrichastrum alpinum, andSanionia georgicouncinata ). To determine whether reducing cold stress increases sexual reproduction as would be predicted if sex is being constrained due to physiological limitations, we counted sporophytes for these four moss species in OTC and control plots during two years. Also, we measured sporophyte size for a smaller sample of sporophytes of two species, B. patens and H. antarctica, in the OTC and control plots. Results After 2 years of the experimental treatment, maximum daily air temperature, but not daily mean air temperature, was significantly higher inside OTCs than outside. We found a significant species by treatment effect for sporophyte production, with more sporophytes produced in OTCs compared with controls forB. patens andP. alpinum . Also, sporophytes ofB. patens andH. antarctica were significantly larger in the OTCs compared with the control plots. Conclusions Our results suggest that the lack of sexual reproduction in these Antarctic mosses is not adaptive but is constrained by current environmental conditions and that ameliorating conditions, such as increased temperature may affect sexual reproduction in many Antarctic mosses, altering moss population genetics and dispersal patterns.